EARNING PER SHARE, BOOK VALUE EQUITY, DAN CASH FLOW OPERATION PADA BUY HOLD ABNORMAL RETURN PRIMARY TREND SAHAM LQ-45 (PERIODE 2010-2012) - Elizabeth Lucky Maretha Sitinjak; Yusni Warastuti; Heribertus Sri Sulistyanto (Jurnal Akuntansi Bisnis, 2014)
The purpose of this study was to investigate the value relevance of accounting information (EPS, BVE, and CFO) against the decision of buying and holding stocks (buy and hold). This study uses regression model with abnormal return (BHAR) to see the value relevance of accounting information on the behavior of buying, selling and holding shares in the Indonesian Capital Market. Sample of companies used in this study, the LQ- 45 firms over three years (2010-2012). The study also looked phases that exist in the primary trend (accumulation phase, a public participation phase, the phase distribution). The results of this study, showing the value relevance of accounting information in the EPS trend of public participation phase.